Real time implementation of energy optimization technique in multimodal surveillance wireless sensor network - Tripathi A.; Gupta H.P.; Shukla K.K.; Jit S.; Dutta T. (My University, 2025)
The energy optimization makes the battery-powered wireless sensor nodes to serve prolonged lifetime in terms of energy. This implies better life-time and economical in nature. To introduce energy optimization techniques in any system, in general, the other performance constraints of the system are compromised. In critical applications such as, surveillance camera system, it is designed in conventional framework to work for 24×7 basis in fully active mode. It consumes huge amount of energy and also acquires big storage space to store the captured image data. It is not suitable for surveillance of impervious sites. In this work, we address this problem and an energy efficient prototype has been proposed based on the passive sensing techniques. Pyro-electric Infrared (PIR) sensors node, which consumes very low power, are used on-demand and ubiquitous wireless sensor network and implemented in real-time at UG Laboratory, Department of Computer Science & Engineering, IIT-BHU. A prototype is designed to optimise the energy requirement for the security watch-keeping of the laboratory by using the two operation modes of security camera with the controller to switch between the modes on the basis of information received over the WSN. The developed prototype conserves energy without compromising the quality of service.